Unprofessional, Dishonorable, and Disgraceful: Sanism and the Ontario Social Work Regulator - Jones, Alison (My University, 2023)
In 2018, the Ontario College of Social Workers and Social Service Workers (OCSWSSW) implemented an additional screening question for prospective social workers registering with the College, requiring applicants to indicate if there is any sign they have a physical or mental condition or disorder that “could affect [their] ability to practice social work in a safe manner.” This Health Declaration policy was created within a broader context of increasing surveillance and punishment of social workers conducted by the College, on the grounds that fitness to practice social work is a bio-moral-medical quintessence that some possess and others lack, and which social work elites must identify in order to “protect the public.” This thesis undertakes a critical discourse analysis of publicly available documents provided by the College. I draw from critical disability studies, anti-colonial scholarship, and postmodern work to establish the College as an organ of the Canadian settler colonial project. I use the term “safe-ability” – distilling the Health Declaration’s language and that of their other rules, communications, and decisions – calling attention to ideological fiction operating within ableist/sanist and colonial logics, the basis of its authority to punish social workers and “protect” the public. The College uses terms like unfit, incapacity, and incompetence to conjure threat of risk throughout their documentation, showing significant investment in broadcasting lies about disabled people. College disciplinary documents show that social workers have been found to be unfit on the basis of statements about their health, inherent abilities, mental/physical examinations, and even charges of unfit conduct outside the scope of their duties as social workers. Legal and medical discourse is invoked to give the appearance of objectivity and to authorize power. I show that the OCSWSSW perpetrates abuses under cover of the fictitious entity “safe-ability” – a colonist ableist/sanist fabrication used to justify and valorize such professionalizing institutions that ought to be abolished.
Keywords: Ableism, Sanism, Colonialism, Social Work, Professional Regulation